Uwagi o międzykulturowych aspektach nauczania języka rosyjskiego jako obcego - Markunas, Antoni; Żebrowska, Anna (Przegląd Rusycystyczny, 2009)
UWAGI O INTERKULTUROWYCH ASPEKTACH NAUCZANIA JĘZYKA ROSYJSKIEGO JAKO OBCEGO Streszczenie Niniejszy artykuł zawiera krótkie rozważania dotyczące znaczenia elementów inter-kulturowych w nauczaniu języka rosyjskiego jako obcego. Efektywna komunikacja przeds-tawicieli odmiennych kultur wymaga zarówno wiedzy językowej, jak i socjokulturowej. Jej posiadanie sprzyja dialogowi odmiennych kultur, rozwojowi młodego człowieka, kształtowaniu tolerancji, otwartości, szacunku nie tylko do cudzej kultury, ale i do własnej. NOTES ON CROSS-CULTURAL ASPECTS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE Summary This article includes a brief discussion on the importance of cross-cultural elements in teaching Russian as a foreign language. Effective communication of the representatives of different cultures requires both linguistic and sociocultural knowledge. Comprehension of this knowledge promotes the dialogue of different cultures, the development of a young man, forming of tolerance, openness and respect not only towards foreign culture, but also to their own.